Association between serum uric acid and motor subtypes of Parkinson's disease. Issue 8 (August 2015) - Lolekha, Praween; Wongwan, Piyanat; Kulkantrakorn, Kongkiat
Abstract: The aim of this study was to evaluate serum uric acid (UA) levels and serum uric acid/creatinine ratios (UA/Cr) in patients with non-tremor dominant (NTD) Parkinson's disease (PD) compared to tremor dominant (TD) PD and healthy controls (HC). UA is believed to have a protective effect on the central nervous system against oxidative damage and neuronal cell death which could impact on progression and motor subtypes of PD. Serum UA levels and UA/Cr were determined in 100 PD patients and 100 age and sex matched HC. Subtypes of PD were classified into TD and NTD. Patients with PD showed statistically significantly lower serum UA ( p  = 0.007) and serum UA/Cr ratios ( p  < 0.001) than HC. Patients with NTD PD had statistically significantly lower serum UA ( p  < 0.001) and serum UA/Cr ( p  = 0.001) than in patients with TD PD. Patients with mild PD severity also had significantly higher serum UA ( p  = 0.015) and serum UA/Cr ( p  = 0.004) than patients with moderate to severe disease. Our study suggests that UA has a pathogenic role in the clinical subtype of PD. Serum UA levels together with serum UA/Cr are potentially useful biomarkers to indicate risk, severity and motor subtype of PD.